Agree to Agree Agreement in the Minimalist Programme (Volume 6) - Hartmann, Katharina; Smith, Peter W.; Mursell, Johannes (Language Science Press, 2020)
Agreement is a pervasive phenomenon across natural languages. Depending on one's definition of what constitutes agreement, it is either found in virtually every natural language that we know of, or it is at least found in a great many. Either way, it seems to be a core part of the system that underpins our syntactic knowledge. Since the introduction of the operation of Agree in Chomsky (2000), agreement phenomena and the mechanism that underlies agreement have garnered a lot of attention in the Minimalist literature and have received different theoretical treatments at different stages. Since then, many different phenomena involving dependencies between elements in syntax, including movement or not, have been accounted for using Agree. The mechanism of Agree thus provides a powerful tool to model dependencies between syntactic elements far beyond φ-feature agreement. The articles collected in this volume further explore these topics and contribute to the ongoing debates surrounding agreement. The authors gathered in this book are internationally reknown experts in the field of Agreement.